2019
DOI: 10.1002/cphc.201801143
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of β‐Ammonium Substitution on the Reaction Kinetics of Aminooxy Condensations with Aldehydes and Ketones

Abstract: The click‐chemistry capture of volatile aldehydes and ketones by ammonium aminooxy compounds has proven to be an efficient means of analyzing the carbonyl subset in complex mixtures, such as exhaled breath or environmental air. In this work, we examine the carbonyl condensation reaction kinetics of three aminooxy compounds with varying β‐ammonium ion substitution using Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS). We determined the activation energies for the reactions of the aminoox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…The apparent kinetic constant of n -7ONEs is quite similar, where the 2–7ONE oximation reaction rate is slightly lower than the 3–7ONE oximation rate. This fact could be explained assuming that the activation energy of the oximation reaction of 2–7ONE is lower because of steric impediments. , …”
Section: Resultsmentioning
confidence: 99%
“…The apparent kinetic constant of n -7ONEs is quite similar, where the 2–7ONE oximation reaction rate is slightly lower than the 3–7ONE oximation rate. This fact could be explained assuming that the activation energy of the oximation reaction of 2–7ONE is lower because of steric impediments. , …”
Section: Resultsmentioning
confidence: 99%
“…On the contrary, the BR of the trans isomer requires the breakage of the bond C 1 – C 2 . This last bond corresponds to an imine vinyl group with a higher electronic density that avoids the attack of the free electron pair of the nitrogen atom. For this reason, this stereoisomer of the oxime is less reactive than the ( Z ) oxime isomer. It could therefore be concluded that ( E )-2-cyclohexen-1-one oxime conversion is almost negligible in the BR step.…”
Section: Resultsmentioning
confidence: 99%
“…The whole training procedure stops till it reaches the set iterations. The bounds for first-principle parameters are set according to the literature study (Ogunwale et al, 2019;Thotla et al, 2007), while the data-driven coefficients were searched in the range of [-0.1, 0.1]. A small range [-0.1, 0.1] was chosen because the first-principle parts play the primary role in the hybrid modeling to explain the complex reaction processes.…”
Section: Hybrid Modelsmentioning
confidence: 99%